Evaluation of Doppler USG and CSF flow wave patterns in the diagnosis of ventriculoperitoneal shunt obstructions - Kaplan, Metin; Yakar, Huseyin; Orhan, Haci; Erol, Fatih S. (Karger, 2007)
Objective: In the present study, our aim was to designate standards for Doppler USG images correlating with dysfunctions in each segment of the ventriculoperitoneal ( VP) shunt. Materials and Methods: For this mechanical study, a platform was formed with pools filled with SF on both sides. Low-, intermediate- and high- pressure shunt mechanisms were placed on this platform. For each shunt system, flow wave pattern was evaluated. Doppler USG was performed when the shunt functioned normally, the peritoneal, ventricular ends and the exit of the valve were obstructed. The results were recorded. Results: When the distal end of the peritoneal catheter was obstructed, no flow wave pattern was observed in Doppler USG. When the exit of the valve was obstructed, no flow pattern was taken from the peritoneal end, either. When the valve was pressed on the ventricular catheter, a second wave pattern with lower amplitude and a wider base was observed, in addition to the wave pattern that was observed when the pressure on the valve was removed. Conclusion: Doppler USG is an effective method for the diagnosis of shunt obstruction. The evaluation of flow wave patterns using this method instead of measuring flow rates creates a different standard for each situation.
Keywords: ventriculoperitoneal shunt; Doppler USG; hydrocephalus